Lck-dependent Fyn Activation Requires C Terminus-dependent Targeting of Kinase-active Lck to Lipid Rafts - Filipp, Dominik (American Society for Biochemistry and Molecular Biology, 2008)
Mechanisms regulating the activation and delivery of function of Lck and Fyn are central to the generation of the most proximal signaling events emanating from the T cell antigen receptor (TcR) complex. Recent results demonstrate that lipid rafts (LR) segregate Lck and Fyn and play a fundamental role in the temporal and spatial coordination of their activation. Specifically, TcR-CD4 co-aggregation-induced Lck activation outside LR results in Lck translocation to LR where the activation of LR-resident Fyn ensues. Here we report a structure-function analysis toward characterizing the mechanism supporting Lck partitioning to LR and its capacity to activate co-localized Fyn. Using NIH 3T3 cells ectopically expressing FynT, we demonstrate that only LR-associated, kinase-active (Y505F)Lck reciprocally co-immunoprecipitates with and activates Fyn. Mutational analyses revealed a profound reduction in the formation of Lck-Fyn complexes and Fyn activation, using kinase domain mutants K273R and Y394F of (Y505F)Lck, both of which have profoundly compromised kinase activity. The only kinase-active Lck mutants tested that revealed impaired physical and enzymatic engagement with Fyn were those involving truncation of the C-terminal sequence YQPQP. Remarkably, sequential truncation of YQPQP resulted in an increasing reduction of kinase-active Lck partitioning to LR, in both fibroblasts and T cells. This in turn correlated with an ablation of the capacity of these truncates to enhance TcR-mediated interleukin-2 production. Thus, Lck-dependent Fyn activation is predicated by proximity-mediated transphosphorylation of the Fyn kinase domain, and targeting kinase-active Lck to LR is dependent on the C-terminal sequence QPQP.